УДК 055 MATHEMATICAL MODEL AND ANALYTICAL SOLUTIONS OF THE PROCESS OF PHYSICS-CHEMICAL HYDRODYNAMICS: MATHEMATICAL MODEL AND ANALYTICAL SOLUTIONS - Ismanova, Klara (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
To describe mathematical models that calculate geo-technological indicators necessary for the management of physical-chemical hydrodynamic processes. Analyzing methods for solving these models and developing analytical solution methods.